Selection Bias, Demographic Effects, and Ability Effects in Common Value Auction Experiments - Casari, Marco; Ham, John C; Kagel, John H (American Economic Review, 2007)
Inexperienced women, along with economics and business majors, are much more susceptible to the winner’s curse, as are subjects with lower SAT/ACT scores. There are strong selection effects in bid function estimates for inexperienced and experienced subjects due to bankruptcies and bidders who have lower earnings returning less frequently as experienced subjects. These selection effects are not identified using standard econometric techniques but are identified through experimental treatment effects. Ignoring these selection effects leads to misleading estimates of learning.